Family Development Theory on Childcare Dual Career Families: Systematic Literature Review - Merida Reformasi; Kukuh Septio Aji; Ika Febrian Kristiana (International Journal Labs, 2022)
Dual-career family is a family phenomenon in which the father and mother both work outside the home so that the practice of parenting involves internal or external parties (eg grandparents, uncles, neighbors, household assistants, or day care). This study is a systematic literature review that aims to examine dual career family parenting. Online databases used: Scient Direct, Google Scholar, Springer, and Sage Journal with the keyword